2016
DOI: 10.1097/ico.0000000000000954
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-29b Overexpression Decreases Extracellular Matrix mRNA and Protein Production in Human Corneal Endothelial Cells

Abstract: Purpose MicroRNAs are small non-coding RNAs which regulate gene expression at the post-transcriptional level. We reported that levels of microRNA (miR)-29 family are decreased in Fuchs endothelial corneal dystrophy (FECD) patient corneas. The miR-29 family regulates production of extracellular matrix (ECM) proteins. Accumulation of ECM proteins in Descemet’s membrane is an important pathologic change in FECD. In this study, we transfected miR-29b into human corneal endothelial cells and tissues and evaluated E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…We performed a GO-term enrichment analysis of miR-29 targets with 8-mer seed matches and found that about half of the top pathways were related to ECM structure or insulin signaling, consistent with miR-29’s previously described roles in liver, cornea, muscle, and heart (Supplementary Fig. 2c) 21,22,23,24 . A closer examination of individual miR-29 targets, ranked by peak height, reveals that 4 of the top 10 genes have been previously validated in other cell types (Fig.…”
Section: Figsupporting
confidence: 81%
“…We performed a GO-term enrichment analysis of miR-29 targets with 8-mer seed matches and found that about half of the top pathways were related to ECM structure or insulin signaling, consistent with miR-29’s previously described roles in liver, cornea, muscle, and heart (Supplementary Fig. 2c) 21,22,23,24 . A closer examination of individual miR-29 targets, ranked by peak height, reveals that 4 of the top 10 genes have been previously validated in other cell types (Fig.…”
Section: Figsupporting
confidence: 81%
“…Recent studies have shown that miRNAs-29a/b/c were involved in osteoclast regulation and could influence expression of certain extracellular matrix molecules i.e. collagens and their modifying enzymes[ 13 17 ]. Previous reports showed an increase in miRNA-29b during osteoclast differentiation in TNF- α / RANKL-treated cells[ 16 ] and promoted osteoclastogenesis by regulating osteoclast commitment and migration[ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs-29a/b/c were involved in regulation of osteoblasts/clasts differentiation and could influence expression of certain extracellular matrix molecules i.e. collagens and their modifying enzymes[ 13 15 ]. Kagiya and Nakamura[ 16 ] found an increase in miRNA-29b during osteoclast differentiation in TNF-α/RANKL-treated cells, suggesting this miRNA plays a role in TNFα -regulated osteoclast differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…We previously identified global DNA methylation changes that occur in the corneal endothelial tissue of FECD patients and specifically observed a high number of DNA methylation alterations occurring in miRNA sequences [30]. This finding was intriguing because prior reports had demonstrated that miRNAs were differentially expressed in the corneal endothelium during aging [58], and that widespread downregulation of miRNA levels occurred in the corneal endothelium of patients with late-onset FECD [36, 59]. Because DNA methylation has been shown to be a mechanism for regulating miRNA expression [33], we performed a sub-analysis of the miRNA DNA methylation array data.…”
Section: Discussionmentioning
confidence: 99%